Crowning glory: public law, power and the monarchy - Murphy, Thérèse; Whitty, Noel (Sage, 2000)
‘New public law’ has a keen interest in the deployment of power and the shifting nature of the public and private. In this article, we argue that the historical legacy of the Crown has hindered the ability of public lawyers to respond to changes in modes of governance in the UK. The constitutional law textbook tradition has played a key role in limiting critiques of the Crown because of the obfuscation that surrounds the legal and political status of the Monarch. However, instead of discounting the significance of the monarchy, we use it as a resource for exploring governing power, the blurring of boundaries and constitutional renewal.